Exporters moving toward emerging markets: A resource-based approach. Issue 5 (19th August 2014) - BORTOLUZZI, GUIDO; Chiarvesio, Maria; Di Maria, Eleonora; Tabacco, Raffaella
Abstract : Purpose: In this study, we aimed to understand whether and how specific capabilities at the firm level can sustain firms during the process of international expansion in emerging markets (EMs). Design/methodology/approach: A quantitative study was carried out, and we analyzed data from a sample of 271 manufacturing firms. A logistic regression was used to check for differences in the endowment of resources and capabilities of firms solely focusing on advanced markets (AMs) or extending their international scope to EMs as well. Findings: Firms that expanded their business in EMs showed a significantly higher endowment of international experience and marketing capabilities compared with firms that focused only on AMs. We found that the size of the firm is irrelevant: Even small firms can reach EMs by leveraging an appropriate set of capabilities. Research limitations/implications: Our study is cross-sectional and cannot provide a longitudinal view of the process of capability development. Future research will be needed to detail the process of capability development during the international expansion of firms into EMs. Practical implications: Regardless of size, firms that plan to enter EMs should develop specific capabilities, especially marketing capabilities, to increase the likelihood of success. Already internationalized firms have a considerable advantage due to the knowledge they have accumulated in other markets. Originality/value: This paper advances understanding of the process of the international expansion of firms in EMs from a resource-based perspective.